Engineering protein self-assembly for biosensing applications - Jo, Suna (My University, 2024)
Protein self-assembly is a promising bottom-up approach to create biological materials with programmable functionalities, particularly for biotechnological applications. This approach leverages engineering recombinant protein building blocks, derived from natural or artificially designed proteins, that possess distinct properties to mediate self-assembly and genetically encode specific functions. In this dissertation, we present a modular system that employs building blocks based on various protein domains and motifs that exhibit self-assembling properties or biosensing capabilities. Functional protein biomaterials were assembled through controlled protein-protein interactions and genetically encoded biosensing functionalities tailored for biomedical and environmental applications. First, we demonstrate a protein coating self-assembly strategy that modularly incorporates functional protein domains. This system exploits the high-affinity coiled-coil interactions and liquid-liquid phase separation of proteins into coacervates. We further investigated the self-assembly conditions to enhance the density and stability of protein coatings and validated this approach across multiple substrate types. By incorporating a fluorescent calcium indicator protein GCaMP into the coating, we demonstrated calcium sensing, enabling the monitoring the calcium levels in biological fluids relevant to hypercalcemia. Second, we explored the cooperative self-assembly of hybrid protein cages designed to encapsulate nanoparticles to control their optical properties for enhanced fluorescent biosensing of calcium ions. We employed temperature-responsive inverse phase transition of proteins to induce the formation of vesicle-like protein cages and investigated the cooperativity between the cage assembly and simultaneous encapsulation of polymer or inorganic nanoparticles. This process resulted in the formation of hybrid spheres with high-density nanoparticle encapsulation. The hybrid cages incorporating the fluorescent calcium indicator protein OGECO-1 exhibited enhanced fluorescent signal intensity and increased sensitivity to calcium ions. Lastly, we engineered protein-based fluorescent biosensors for nitrite detection, employing a Förster Resonance Energy Transfer (FRET) system. A nitrite-binding protein complex, NasS-NasT, was coupled with a fluorescent protein FRET pair, and the dissociation of this complex in response to nitrite binding was used to generate FRET signals for nitrite sensing in live bacteria. We extended this system into a cost-effective nitrite sensing platform by creating coating materials. Molecular docking simulations were performed to understand the binding interactions between NasS and nitrite, guiding the introduction of mutations to enhance sensitivity. Additionally, structural modeling identified promising mutations to further refine the FRET sensor, extending its applicability to detect relevant targets such as hydroxylamine. Overall, this work demonstrates the application of protein self-assembly for constructing protein-based biomaterials and tools for biosensing. The modular self-assembly platform was designed and investigated to integrate various biosensor proteins, enabling the detection of ions relevant to healthcare and environmental monitoring. This research establishes a solid foundation for advancing in recombinant protein self-assembly for innovations in biosensor technology across diverse fields.
Keywords: Protein engineering; Biosensor; Self-assembly